(X) = 3x + 1 עם f: R -> R. מצא פונקציה ליניארית h: R -> R כך: h (f (x)) = 6x - 1?

(X) = 3x + 1 עם f: R -> R. מצא פונקציה ליניארית h: R -> R כך: h (f (x)) = 6x - 1?
Anonim

תשובה:

#h (x) = 2x-3 #

הסבר:

# "מאז" h (x) "היא פונקציה ליניארית #

# "let" h (x) = ax + b #

#rArrh (f (x)) = a (3x + 1) + b #

#color (לבן) (rArrh (f (x))) = 3ax + a + b #

.# "now" h (f (x)) = 6x-1 #

# rArr3ax + a + b = 6x-1 #

#color (כחול) "להשוות מקדמים של מונחים דומים" #

# rArr3a = 6rArra = 2 #

# a + b = -1rArr2 + b = -1rArrb = -3 #

#rArrh (x) = ax + b = 2x-3 #